Musim pemijahan dan ukuran layak tangkap udang jerbung (Penaeus merguiensis) di perairan Dumai dan sekitarnya, Riau - Putri Pane, Andina Ramadhani; Suman, Ali (Universitas Riau, 2020)
The high demand for shrimp commodities will increase catching to spur production so that it will affect the shrimp population. This scientific study will discuss the spawning season of banana shrimp (Penaeus merguiensis), catch size, and environmental conditions of Dumai and surrounding waters. This research was conducted from April to December 2018 using survey methods around the waters of Dumai, Riau. Data collection was carried out monthly on 4,677 banana shrimps assisted by enumerators. The analysis was carried out on the relationship between carapace length and body weight, sex ratio, gonad maturity level, and catch size. The condition of the aquatic environment that influences the process of reproduction becomes a comparison in determining management efforts. Banana shrimp size structure 18-60 mm, dominant at 28 mm and negative allometric growth patterns. The genital ratio shows that female shrimp are more dominant than males and the spawning season lasts throughout the year with peaks in June and December. The length at first capture was 34.5 mm with the length at first maturity was 30.8 mm (Lc> Lm), meaning that it had spawned before being capture. However, the polluted water environment can interfere with the process of growth and population growth even though various environmental parameters are still within normal limits. So the thing to do is to close the shrimp catching area in June and December, not catch in the spawning area, the size of the shrimp that can be caught is 31 mm and protect the aquatic environment from pollution.